O "línter humano": militância católica, mendicância e a Cidade Ozanam Belo Horizonte : 1900-1938 - Fernando Rosa do Amaral (2017)
This Masters thesis aims to analyze the actions undertaken by the government of the city of Belo Horizonte and the movement of lay Catholics from the period 1900 to 1938 on the question of the beggars of the city. This temporal cut marks the reaction of the Catholic Church against the Process of secularization that marked the beginning of the brazilian Republic. In order to restore a prominent position at the scenario religious and political, the episcopate encouraged the formation of a Catholic militancy centered with the objective of defending the precepts of the Church in public spaces and political debates of the country. From the 1920s, Catholic discourse gained greater repercussion, being appropriated by various political leaders throughout the country. However, it was more precisely in the Vargas Era (1930-1945) that the Catholic Church achieved a stronger alliance with the State. On the other hand, in Minas Gerais, an approximation between political and ecclesiastical authorities was already consolidated in the 1920s, especially during the government of Antônio Carlos (1926-1930). The presence of Dom Cabral in Belo Horizonte was decisive for an approach of the Catholic Church with the politicians of Minas Gerais. The bishop of the capital founded the Catholic press, organized congresses and organized the militancy of the laity, giving greater visibility to the actions undertaken by Catholic leaders, such the confrere vicentino Furtado de Menezes. Among a great diversity of associations that acted in the city, the associations that aimed to provide assistance to the poor stood out. From 1900, the city hall of Belo Horizonte was seeking the solution to the question of the beggars of the city. However, the measures implemented by the municipal authorities to regulate the presence of beggars in the urban area between 1900 and 1930 were not efficient. From the growth of the Catholic discourse in the city, the City Hall and the State Government, strongly influenced by Dom Cabral, began to give financial and material incentives to the welfare works existing in the capital. At this context, marked by a strong population growth and a great urban expansion, was developed the project of the Ozanam City, with the purpose of erecting a city "apart" the city for the beggars, where they would receive shelter, food, hygiene and would be moralized by their conversion into labor power. The creation of the Ozanam City and its format of assistance to the poor were a direct result of the rapprochement between Catholics and politicians, which contributed decisively to the fact that Belo Horizonte was thus viewed as a modern and Catholic city